Perubahan Sosial, Ijtihad dan Dinamika Hukum Islam - Salamah Eka Susanti (Asy-Syari’ah : Jurnal Hukum Islam, 2018)
The Qur'an contains only a small number of detailed laws, while the sunna is limited to the cases that occurred in its time, so to solve new problems, ijtihad is required. In such a connection for a Muslim, new problems arising from the progress of science and technology, should not be confronted with confrontational passages, but must be solved by ijtihadi.Karena reality often occurs, that the development of society and public opinion faster the pace of the road from on the development of the law itself. The dynamics of people's lives are characteristic of change. Through the power of intention, power, and creativity, humans create cultural objects as a result of their creations. Changes that occur in society when observed can occur in various There are slow changes (evolution) and there are rapid changes (revolution). The social changes that occur in a society, directly or indirectly, affect institutions in various fields, such as government, economics, education, religion and so on. The continuation of an impact on the social system changes. When the law is faced with social change, it occupies one of its functions, which can function as a means of social control, and the law can serve as a means of social change. the characteristics of the law above is due to the inconsistency of social dynamics and the dynamics of law in the life of society. Unequaled dynamics of society and law, usually will bring social lag. From here, then comes a question whether Islamic law as a norm of God's determination can experience changes in accordance with the needs of the community? Ijtihad is an important factor for the development and development of Islamic law.Ijtihad done to answer the problems that arise in society that is not yet known legal status.ijtihad has a wide scope, the issues are not regulated explicitly dala m al-Qur'an and sunna can be done ijtihad. In order for humans to have breadth in determining its activities according to its ability, needs and environment. Therefore ijtihad in the field of Islamic law in anticipating the dynamics of society and social changes concerning the values, behavior patterns, and social system of a society is a concern in establishing Islamic law. Thus ijtihad is the third source in the development of Islamic law. Keywords: Social Change, Ijtihad, Law, Islamic.